2006
DOI: 10.1021/jp063679n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Activity Analysis of Catalytic Water Oxidation Induced by Hybridization of [(OH2)(terpy)Mn(μ-O)2Mn(terpy)(OH2)]3+ and Clay Compounds

Abstract: Hybridization of [(OH(2))(terpy)Mn(mu-O)(2)Mn(terpy)(OH(2))](3+) (terpy= 2,2':6',2' '-terpyridine) (1) and mica clay yielded catalytic dioxygen (O(2)) evolution from water using a CeIV oxidant. The reaction was characterized by various spectroscopic measurements and a kinetic analysis of O(2) evolution. X-ray diffraction (XRD) data indicates the interlayer separation of mica changes upon intercalation of 1. The UV-vis diffuse reflectance (RD) and Mn K-edge X-ray absorption near-edge structure (XANES) data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 29 publications
5
75
0
Order By: Relevance
“…52, 53 In contrast, increasing the loading of Mn catalysts within a layered material enhances the rate of oxygen generation. 45 Thus, the incorporation of recently reported Mn catalysts 41 into these polymer layers may lead to practical success at higher catalyst concentration. The potential of this approach has been demonstrated by our own recent work on a photocatalytic assembly that utilised a bio-inspired cubane cluster as water oxidation catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…52, 53 In contrast, increasing the loading of Mn catalysts within a layered material enhances the rate of oxygen generation. 45 Thus, the incorporation of recently reported Mn catalysts 41 into these polymer layers may lead to practical success at higher catalyst concentration. The potential of this approach has been demonstrated by our own recent work on a photocatalytic assembly that utilised a bio-inspired cubane cluster as water oxidation catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytic turnover is not attained when Ce(IV) is used as the oxidant due to the low pH required for use of Ce(IV) as an oxidant which causes deactivation of the catalyst [96]. In contrast to the single-turnover oxygen evolution by the homogeneous system using Ce(IV), 7 has been shown to evolve oxygen catalytically using Ce(IV) when it is supported on a clay mineral [97,98]. The dramatic improvement of 7 in heterogeneous versus homogenous systems with Ce(IV) is proposed to be the result of the stabilizing clay environment which prevents the dimer from dissociating into monomers.…”
Section: [(Tpy)(h 2 O)mn(o) 2 Mn(h 2 O)(tpy)] 3+ -mentioning
confidence: 99%
“…The presence of the trifluoroacetate ligands may prevent the formation of a possible Mn V O species. Despite these solution studies, Yagi has shown that these water oxidation catalysts are effective when placed on a clay surface [157].…”
Section: Proposed Catalytic Dinuclear Mn Modelsmentioning
confidence: 99%